(untitled) (LEGAL DIALOGICA, 2025)
This study aims to analyze the legal accountability regarding the exploitation of children as illegal parking attendants in Makassar City, and to identify the factors influencing children’s involvement in such work. The research employed an empirical legal approach, collecting primary data from field studies, supported by secondary legal materials. The findings show that the recruitment of children for forced labor in parking services constitutes an act of exploitation as regulated under Article 2 paragraph (1) and Article 4 of Law No. 21 of 2007 on the Eradication of Human Trafficking, with criminal sanctions ranging from 3 to 15 years imprisonment and fines from IDR 120 million to IDR 600 million. Factors leading children into this work include poverty, lack of education access, minimal parental supervision, absence of social protection, low awareness of children’s rights, and peer influence. The study recommends preventive and repressive measures by relevant authorities to ensure children enjoy their rights to education and a safe upbringing. Abstrak: Penelitian ini bertujuan untuk menganalisis pertanggungjawaban hukum terhadap praktik eksploitasi anak sebagai tukang parkir liar di Kota Makassar serta mengidentifikasi faktor-faktor yang mempengaruhi keterlibatan anak dalam pekerjaan tersebut. Jenis penelitian yang digunakan adalah penelitian hukum empiris dengan mengumpulkan data primer dari lapangan, didukung oleh bahan hukum sekunder. Hasil penelitian menunjukkan bahwa tindakan merekrut anak untuk kerja paksa pada layanan parkir merupakan bentuk eksploitasi sebagaimana diatur dalam Pasal 2 ayat (1) dan Pasal 4 Undang-Undang Nomor 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang, dengan sanksi pidana penjara 3–15 tahun dan denda Rp120 juta hingga Rp600 juta. Faktor yang mempengaruhi anak bekerja di sektor ini meliputi kemiskinan, keterbatasan akses pendidikan, minimnya pengawasan orang tua, ketiadaan perlindungan sosial, rendahnya kesadaran hak anak, dan pengaruh teman sebaya. Rekomendasi penelitian ini mencakup langkah pencegahan dan penindakan oleh pihak berwenang guna menjamin hak anak untuk memperoleh pendidikan dan tumbuh dalam lingkungan yang aman.